Use of metal-organic framework to remove chromium (VI) from aqueous solutions - Noraee, Zahra (J Environ Health Sci Eng, 2019)
Chromium is one of the heavy metals found in industrial wastewaters, which have highly toxic to human beings and the environment. Exposure with it may cause some hazard diseases including stomach ulcers, liver, vomiting, kidney and nerve tissue damage, cancer in the lungs, and eventually death. The main objective of this study was to evaluate the efficiency of Uio-66 and ZIF-8 in removing chromium from aqueous solutions. For the synthesis of Uio-66 and ZIF-8, hydrothermal and sol-gel methods were used, respectively. The prepared Uio-66 and ZIF-8 were identified by FTIR, XRD, FE-SEM, EDX, and BET. All experiments were done in batch conditions. Uio-66 and ZIF-8 efficiency for chromium adsorption from aqueous solutions were investigated by variables like initial concentration (10–200 mg/l), pH (3 to 11), Uio-66 and ZIF-8 dosage (0.2 to 1 g/l) and contact time (45 min). The FE-SEM image showed that the sizes of Uio-66 crystals were between 140 and 280 nm. The specific surface area and total pore volume of the prepared Uio-66 and ZIF-8 were 800 m(2)/g, 0.45 m(3)/g, 1050 m(2)/g, and 0.57 m(3)/g, respectively. The results show chromium adsorption has increased in acid conditions. Equilibrium dosage for Uio-66 and ZIF-8 was 0.4 g/l and 0.6 g/l, respectively. Adsorption equilibrium was performed after 60 min and after this time, chromium adsorption did not significantly change. The study results showed that the experimental data obtained fitted with kinetic model pseudo-order- reaction and isotherm model of Langmuir.